The effect of educational games using educandy on elementary school students' learning motivation - Non Syafriafdi; Elni Yakub; Tri Umari; Suarman; Isnaria Rizki Hayati; Dina Puspita; Putri Cahyani Pernandes (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research investigates the effect of utilizing the Educandy educational game platform on the learning motivation of elementary school students at SD 035 Tarai Bangun, Tambang District, Kampar Regency. The study employed a quasi-experimental one-group pretest-posttest design to evaluate the effectiveness of Educandy in boosting students' motivation. The research subjects were selected using purposive sampling, and data were gathered through a validated motivation questionnaire. The results indicated a significant improvement in students' motivation, with post-intervention scores averaging higher than pre-intervention scores. The statistical analysis, using the Wilcoxon Signed-Rank Test, confirmed that the use of Educandy games had a positive influence on learning motivation, with an N-gain categorized as moderate. This finding suggests that Educandy games can serve as a practical alternative for enhancing students' learning motivation in elementary education.